2003
DOI: 10.1002/uog.11
|View full text |Cite
|
Sign up to set email alerts
|

Fetal cardiac function assessed by Doppler myocardial performance index (Tei Index)

Abstract: Objectives The Tei Index (TI) is a useful, non-invasive

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
169
8
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(193 citation statements)
references
References 17 publications
(38 reference statements)
10
169
8
6
Order By: Relevance
“…In addition, our results for the MPI, although slightly higher, fall within the SDs of those from another study in the literature from early pregnancy, which found MPIs of 0.378 ± 0.110 and 0.352 ± 0.115 in the left and right ventricles, respectively. 11 Friedman et al 7 suggested that global left ventricular function could be evaluated from a single Doppler waveform incorporating inflow and outflow simultaneously. We found that this was also possible in the right ventricle because of the proximity of the inflow and outflow tracts at this early gestation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our results for the MPI, although slightly higher, fall within the SDs of those from another study in the literature from early pregnancy, which found MPIs of 0.378 ± 0.110 and 0.352 ± 0.115 in the left and right ventricles, respectively. 11 Friedman et al 7 suggested that global left ventricular function could be evaluated from a single Doppler waveform incorporating inflow and outflow simultaneously. We found that this was also possible in the right ventricle because of the proximity of the inflow and outflow tracts at this early gestation.…”
Section: Discussionmentioning
confidence: 99%
“…This index is an estimate of global left ventricular function in normal sinus rhythm, as previously described. 31 Previously reported normal values were used for comparison. Specifically, in 56 normal pregnancies, 2 SD above the upper limit of normal for the PR interval (pulsed Doppler echocardiographic assessment of the fetus, validated at birth by simultaneous ECG of the neonate) was 140 ms; 3 SD above the upper limit of normal (Ͼ99% CI) was 150 ms. 30 The method, which is independent of heart rate and gestational age, was subsequently validated by site investigators.…”
Section: Enrollment and Follow-up Visitsmentioning
confidence: 99%
“…31 The presence or absence of tricuspid valve regurgitation was noted and graded as mild if the regurgitant jet filled Ͻ25% of the right atrial area or moderate to severe if it exceeded this value. 23 ECG measurements obtained at birth and 1 year were descriptively compared with normal values for ECGs, 34 including heart rate, PR interval, QRS duration, and QT and QTc intervals.…”
Section: Enrollment and Follow-up Visitsmentioning
confidence: 99%
“…The methodology for the measurement of MPI has been developed over time by researchers studying various foetal pathologies. For example, Freidman et al [7] proposed that LVMPI should be calculated from a single recording of the Doppler wave, representing both the outflow and inflow to the LV. This would allow simultaneous calculation of the isovolumetric contraction time (ICT) and the isovolumetric relaxation time (IRT) [7].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Freidman et al [7] proposed that LVMPI should be calculated from a single recording of the Doppler wave, representing both the outflow and inflow to the LV. This would allow simultaneous calculation of the isovolumetric contraction time (ICT) and the isovolumetric relaxation time (IRT) [7]. To improve accuracy of the MPI measurement, Raboisson et al [8], and later Hernandez-Andrade et al [9], developed the MPI modification (Mod-MPI), in which the opening and closing movements of the aortic valve (AV) and mitral valve (MV), or clicks, were used as the reference points for the measurement of ICT and IRT.…”
Section: Introductionmentioning
confidence: 99%